Application Based Production Management System In Textile Industries - et al., Yoganathan. N. S (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Presently, there is lack of proper management system to manage orders and analyze the daily reports which is prerequisite to acquire production management systems. This paper objectives to elucidate the production management system in small and medium sized Enterprises manufacturing apparent in India. SMES rely invariably on register and manual - data sheet based management which are detrimental in the management process. This proposed system provides a cost-effective solution to the above said problem through app-based platform, it reveals the production planning through reports of the data collected to analyze the daily production on various parameters involved in apparel production. This system provides a daily report to the authorized person (Owner/ Supervisor) to facilitate production management and solve issues pertaining to production output addressing various implements involved in the process.